Dietary exposure assessment of Chinese population to tetrabromobisphenol-A, hexabromocyclododecane and decabrominated diphenyl ether: Results of the 5th Chinese Total Diet Study. (October 2017) - Shi, Zhixiong; Zhang, Lei; Zhao, Yunfeng; Sun, Zhiwei; Zhou, Xianqing; Li, Jingguang; Wu, Yongning
Abstract: Based on the 5th Chinese Total Diet Study (TDS) carried out in 2011, the dietary exposure of Chinese population to three currently used brominated flame retardants (BFRs), tetrabromobisphenol A (TBBPA), hexabromocyclododecane (HBCD) and decabrominated diphenyl ether (BDE-209), was estimated and the related health risks were assessed. Levels of the three BFRs were determined in 80 composite samples from four animal-origin food groups. The average levels of BFRs in various food groups ranged from 0.671 to 5.76 ng/g lipid weight (lw). The levels of TBBPA were lower than those of HBCD but higher than those of BDE-209. Moreover, average contamination levels of TBBPA and HBCD in TDS 2011 were found to be 3 to 30 times higher than those observed in TDS 2007 in the four food groups, indicating an increase in TBBPA and HBCD in the environment during 2007–2011. The average estimated daily intakes (EDIs) of TBBPA, HBCD and BDE-209 via food consumption for a "standard Chinese man" were 1.34, 1.51 and 0.96 ng/kg bw/day, respectively. Meat and meat products were found to be the major contributor to the daily dietary intake because the consumption of meat and meat products were significantly higher than that of other food groups in China. In comparison, the levels and EDIs of BFRs in this study were found to be higher than those in most studies worldwide. However, the large margin of exposure (MOE), with at least 1.1 × 10 5 calculated following the European Food Safety Authority (EFSA) approach, indicates that the estimated dietary exposure to these three BFRs is unlikely to raise significant health concerns. In addition, a comparison between the contamination levels of TBBPA, HBCD, BDE-209 and some novel BFRs in food samples from TDS 2011 indicated an obvious shift in the industrial production and usage pattern between PBDE and non-PBDE BFRs in China. Graphical abstract: Highlights: In a national survey, TBBPA, HBCD and BDE-209 were measured in food composites collected from 20 provinces of China. An obvious shift in the consumption pattern was found between PBDE and non-PBDE BFRs in China. Contamination levels of TBBPA and HBCD in environment increased rapidly from 2007 to 2011. The current estimated dietary exposures of BFRs are unlikely to raise significant health concerns. Abstract : An obvious shift in the consumption pattern was found between PBDE and non-PBDE BFRs in China.